What's in it for me? How blame and credit expectations affect support for innovation. (April 2023) - Timeus, Krista; Breaugh, Jessica
The article applies an experimental vignette research design to test how blame and credit expectations affect individuals' willingness to support innovative programs. Respondents received a survey with three scenarios of innovative programs and were randomly allocated to being blamed if the program failed, credited if it succeeded, or a control group. Blame and credit framing had no statistically significant effect on willingness to support the programs. It was much more important for respondents whether the program was 'good for the community'. This calls into question current assumptions about anticipatory blame avoidance motivations as a primary antecedent of innovative behavior.